PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS VIII SMP ADABIAH PADANG - Satriani; Emidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study had three objectives. First, to describe the poetry writing skills of eighth-grade students at SMP Adabiah Padang before the implementation of the Project Based Learning model assisted by series picture media. Second, to describe the poetry writing skills of the students after the implementation of the Project Based Learning model assisted by series picture media. Third, to analyze the effect of the Project Based Learning model assisted by series picture media on the poetry writing skills of eighth-grade students at SMP Adabiah Padang. This research was motivated by the low level of students' poetry writing skills, particularly in determining themes, selecting appropriate diction, arranging rhyme and rhythm, and developing the depth of meaning in poetry. This study employed a quantitative approach using an experimental method with a One-Group Pretest–Posttest Design. The population consisted of all eighth-grade students of SMP Adabiah Padang in the 2025/2026 academic year, totaling 109 students. The sample comprised 36 students from Class VIII.2, selected through purposive sampling. The research instrument was a performance test in poetry writing. The data were analyzed using normality, homogeneity, and hypothesis testing (t-test). The results showed that the students' poetry writing skills before the implementation of the Project Based Learning model assisted by series picture media obtained a mean score of 43.92, which was categorized as Poor. After the implementation of the model, the mean score increased to 80.90, which was categorized as Good. The results of the hypothesis test indicated that the calculated t-value (t₍count₎) was greater than the critical t-value (t₍table₎) at the 0.05 significance level. Therefore, the alternative hypothesis (H₁) was accepted and the null hypothesis (H₀) was rejected. It can be concluded that the Project Based Learning model assisted by series picture media had a significant positive effect on the poetry writing skills of eighth-grade students at SMP Adabiah Padang.